The Relationship Between The Exchange Rate and The Price Elasticity of Demand for Some Imported Intermediate Goods in Iraq for The Period 2010-2021 - Khaleel Ibraheem, Ban; Mustafa Abdul Hameed, Manahel (Journal of Economics and Administrative Sciences, 2024)
The research provides several analyses, scientific evidence, and theoretical evidence, which clarify the relationship between the exchange rate in Iraq and the import of a group of intermediate goods for the period 2010-2021, as the research problem is represented by the problems and obstacles that caused a decline in the level of local production, and which contributed to an imbalance in output. GDP, and then an imbalance in the (non-oil) trade balance within the current account of the balance of payments. The research discussed the basic concepts of the exchange rate and its determination mechanism, price elasticity, intermediate goods and the relationship between these variables. After that, price elasticity coefficients were arrived at for three intermediate goods imported to Iraq: ordinary cement, resistant cement, and diesel oil for engines, according to the price elasticity formula, according to partial economic theory. The research aims to reveal the response of local demand for these goods through the effect of the exchange rate in Iraq, which translates the prices of these goods locally.Moreover, a statement: Does the exchange rate in Iraq support local production by importing these goods? Is there a commitment to control border crossings and internal price control to prevent monopoly? What is the role of documentary credits as a tool for financing imports in Iraq? The research results showed that the exchange rate in Iraq needs to consider the necessity of these goods and their competition with local production. Paper Type: Research Paper.